ZOOPLANKTON KEANEKARAGAMAN ZOOPLANKTON SEBAGAI INDIKATOR KUALITAS DANAU SIPIN KOTA JAMBI SEBAGAI PENGAYAAN PRAKTIKUM TAKSONOMI MONERA DAN PROTISTA - Pangestu, Retno; SUKMONO, TEDJO; HARLIS, HARLIS (Universitas Jambi, 2020)
Abstract. This study aims to determine the diversity of zooplankton in Lake Sipin. This study uses a descriptive exploratory method by determining the location by purposive sampling. The results showed that found 6 zooplankton classes, namely: Tubulinea, Monogononta, Maxillopoda, Euglenophyceae, Imbricatea, and Eurotatoria consisting of 15 types, namely: Arcella sp., Difflugia globulosa, Difflugia limnetica, Difflugia pyriformis, Asplanchna sp., Brachionus sp., Cyclopoid sp., Macrocyclops varians, Trachelomonas rachiborskii, Euglypa cristata, Polyartha trigla, Trichocerca sp., Trichocerca birostris, Trichocerca bicristata. Abundance ranges from 0.0031 Ind / L - 0.0051 Ind / L; Evenness index ranges from 0.876 - 0.915; diversity index 1.41 - 2.164; and a dominance index of 0.128 - 0.292. Diversity is classified as moderate because the diversity index obtained is greater than 1 and smaller than 3 and no species dominates. It can be concluded that the highest diversity is found in the Tubulinea class. Lake water quality can be tolerated by zooplankton because it tends to have good value. Researchers are advised to conduct research at night to see the relationship between the distribution of zooplankton with the intensity of sunlight, as well as conducting research by determining the location of more diffuse points.